2022
DOI: 10.3390/pharmaceutics14020403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultramicronized N-Palmitoylethanolamine Supplementation on Tramadol and Oxycodone Analgesia and Tolerance Prevention

Abstract: Chronic pain management requires increasing doses of opioids, the milestone of painkillers, which may result in the onset of tolerance with exacerbated side effects. Maintaining stable analgesia with low doses of opioids is thus imperative. N-palmitoylethanolamine (PEA) is an endogenous lipid compound endowed with pain-relieving as well as anti-inflammatory properties. The ultramicronized formulation of PEA was recently demonstrated to be able to modulate morphine’s effects, delaying tolerance and improving ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Clinically speaking, these are very significant results since other antinociceptive or analgesic drugs widely used, such as morphine, tramadol or oxycodone, present several limitations and side effects such as tolerance after repeated administration both in naïve animals [ 39 , 40 , 41 ] and in mice and rats treated with paclitaxel [ 42 , 43 ]. To support the active role of CAIs against chemotherapeutic side effects, in a recent work, CAIs for the IX isoform were introduced into platinum prodrugs to boost cisplatin and oxaliplatin antitumor activity, but it has also been observed that the systemic side effects of platinum drugs were consistently reduced [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clinically speaking, these are very significant results since other antinociceptive or analgesic drugs widely used, such as morphine, tramadol or oxycodone, present several limitations and side effects such as tolerance after repeated administration both in naïve animals [ 39 , 40 , 41 ] and in mice and rats treated with paclitaxel [ 42 , 43 ]. To support the active role of CAIs against chemotherapeutic side effects, in a recent work, CAIs for the IX isoform were introduced into platinum prodrugs to boost cisplatin and oxaliplatin antitumor activity, but it has also been observed that the systemic side effects of platinum drugs were consistently reduced [ 44 ].…”
Section: Resultsmentioning
confidence: 99%